1995
DOI: 10.1039/an9952000887
|View full text |Cite
|
Sign up to set email alerts
|

Plasma, granulocyte and mononuclear cell copper and zinc in patients with diabetes mellitus

Abstract: The concentrations of Cu and Zn were determined in the plasma, granulocytes and mononuclear cells of 26 patients with diabetes mellitus and 26 age and sex-matched controls. In addition, Cu was measured in both washed and unwashed red blood cells, and Cu,Zn-superoxide dismutase (SOD) activity measured in washed red blood cells. Cu and Zn were determined by Zeeman-effect graphite furnace atomic absorption spectrometry following separation of plasma and red blood cells, and the white blood cell fractions (granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 15 publications
5
25
0
2
Order By: Relevance
“…At the same time, zinc is a critical component of the catalytic site of .300 enzymes, implicated in synthesis, storage, and secretion of insulin, as well as being a signaling molecule after insulin secretion (5). Some studies have investigated possible associations between zinc status and diabetes; most reported that patients with diabetes had lower serum/plasma zinc levels (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Interactions Between Zinc Transporter-8 Gene (Slc30a8) and Pmentioning
confidence: 99%
“…At the same time, zinc is a critical component of the catalytic site of .300 enzymes, implicated in synthesis, storage, and secretion of insulin, as well as being a signaling molecule after insulin secretion (5). Some studies have investigated possible associations between zinc status and diabetes; most reported that patients with diabetes had lower serum/plasma zinc levels (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Interactions Between Zinc Transporter-8 Gene (Slc30a8) and Pmentioning
confidence: 99%
“…Mean HbA1c was higher in cases(7.03 ± 0.67%) than controls (5±0.29%), with p<0.001*. Williams et al, [21] reported DM to be a condition most frequently associated with hypozincemia, where they observed 17% decrease in serum zinc concentration in diabetics, compared with controls. The findings of the present study are consistent with Reefat et al, [28] who showed negative correlation between serum zinc concentration and baseline HbA1c% value in cases.…”
Section: Results and Discussion:-mentioning
confidence: 92%
“…In a group of age/sex matched diabetic and normal subjects, cellular loss of zinc was documented from granulocytes as a marker for intracellular zinc status for the body in general in otherwise healthy individuals. Plasma Zn was 17% lower in the diabetic group than the control group but intra-cellular Zn differences did not reach statistical significance suggesting that the renal effects may be predominant in the eventual production of total body Zn depletion in diabetes (Williams et al, 1995). While hyperzincuria is almost uniformly found in diabetes, decreases in tissue.…”
Section: Effects Of Diabetes On Zinc Metabolismmentioning
confidence: 82%